Vegetation Ecology. - Van der Maarel, Eddy (John Wiley & Sons, 2009)
Vegetation Ecology is a comprehensive account of plant communities and their environments. Written by leading experts in their field from four continents, this up-to-date, innovative text:.:.; covers the composition, structure, ecology, diversity, distribution and dynamics of plant communities, with an emphasis on functional adaptations to the abiotic and biotic processes governing plant communities;.:.; reviews the modern developments in vegetation ecology in a historical perspective;.:.; presents a coherent view on vegetation ecology while integrating population ecology, dispersal biology, b.